PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS MODEL PEMBELAJARAN REACT PADA POKOK BAHASAN TRANSFORMASI UNTUK PESERTA DIDIK KELAS IX SMP - VANI ARISA (Departemen Matematika, 2021)
According to conclusion of preliminary research in ninth-grade showed that the most of the mathematics learning outcomes have not qualify the mark determined and they were passive in the learning process. The factor of this case caused by learning tools still not optimal. Based on this situation, researcher doing development on the mathematic’s learning tools, as like as lesson plan (RPP) and student’s worksheets (LKPD) on REACT learning model to supply learning experiences and great effect in student’s learning activities as long as learning process. In this research, researcher were collected the data through of observation, teachers interview, and another coherent research sources. The main research’s subjects are students in ninth of junior high school with different cognitive ability. This research based on plomp design, this design contain are preliminiary research phase, prototype phase, and assessment phase. Come from result of data analysis proved that REACT learning tools was qualify as very valid criteria of content and construction, afterthat itself qualify to practical criteria of execution and effectiveness in time use according to students questionnaires. Keywords—Development design research, learning tools, REACT learning mode, transformation